Client value in procured construction services: New Zealand participants' perspective - Aliakbarlou, S; Wilkinson, S; Costello, SB; Rotimi, JOB (New Zealand Built Environment Research, 2014)
Motivation: Due to the lack of a practical evaluation method to assist clients with measuring value in construction services when hiring service providers, there is greater emphasis on price rather than clients’ values. Hence, this study was undertaken as a response to the above need. The research expects to deliver information needed to drive favourable outcomes through better understanding of clients’ values about contractor and consultant services in the New Zealand construction industry. Knowledge gap: Understanding of clients’ values is identified in New Zealand as one of the important knowledge gaps and key research questions that empirical research projectsshould focus on. The current research addresses the lack of non-price criteria and their measurement criteria based on clients’ values in the New Zealand construction industry. Aim and objectives: The research aims to provide an overview of opinions of New Zealand construction industry participants regarding clients’ values on procured services. The first objective is to evaluate the current level of understanding of clients’ values in New Zealand construction industry. The second objective is to determine limitations of considering clients’ values in procured services evaluation. Research method: Open ended interview questions were used to conduct semi-structured interviews with key construction project decision makers such as clients, consultants, and contactor organizations in New Zealand. The questions were sent to the interviewees via email, before the interview. The qualitative collected data received was analyzed by means of content analysis. Preliminary or anticipated finding: The research provided an overview of opinions of individual practitioners regarding clients’ values on purchased services. Research significance: The investigation identified several areas where practice could be improved for service provider assessments. The research contributes to knowledge in the area of organisational decision making and consequently the psychology of making judgements.
Keywords: Client value; Construction; Service provider